Energy efficiency as a function of changing building form in sustainable rural architecture - Ergin, Şefika; Çorapçıoğlu, Kemal; Balo, Figen (World Scientific Publishing Co. Pte. Ltd., 2021)
Each type of rural building example has different materials and construction techniques based on the geographic and topographic conditions of their location. This generates unique architectural identities that are also shaped by cultural norms of the region. While rural buildings are in the same climate zone, they can have different planning types and configurations. Different types of building form can also be seen in close settlements. This diversity is born of optimal adaptation to climatic comfort conditions, depending on the differences in construction materials. For this reason, the most effective parameters in evaluating performance differences are a range of housing types, space organizations, building forms, construction systems, and material types used. Conventional architecture would suggest that efficient design thinking creates appropriate climatic conditions without utilizing excessive power. The building forms' thermal efficiency, which is produced from traditional architecture, is assessed within the characterized settlement textures and the conclusions existing. The interplay between energy loads, building form, and settlement texture will help to drive the evolved architecture that will enhance efficiency even further. This paper proposes to investigate the settlement texture and building form's impact on energy efficiency by analyzing the project characteristics of traditional Diyarbakır, Turkey, rural area buildings. This will be conducted through the Ecotect simulation program. The quality and quantity of the add-on architectural plans in rural houses in Diyarbakır were analyzed in terms of their energy efficiency. The intent is to preserve and maintain rural architectural identity elements shaped by the data obtained from the physical and natural environment. In this way, two exemplary rural architectures have been studied to educate designers in the ways of livable and energy-efficient space creation- while maintaining a sustainable and traditional rural culture. The buildings' outer surface area and volume were increased incrementally. The first of the house types investigated was enlarged in three stages and the second in four stages. Comparing the A/V ratio in the first stage and the area/volume ratio in the last stage, House1 and House2 achieved 42.93% and 75.96% energy efficiency at life space, respectively. © 2020 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Building form variation; Energy efficiency; Rural architectureID:c06-p035; Sustainable architecture; Traditional buildings